2006
DOI: 10.1159/000096317
|View full text |Cite
|
Sign up to set email alerts
|

Driving Abilities in Frontotemporal Dementia Patients

Abstract: Objective: To evaluate driving competency and the relationship between neuropsychiatric symptoms and driving behavior in frontotemporal dementia (FTD) patients. Methods: Fifteen patients with a diagnosis of FTD and 15 healthy controls were administered a driving simulation task. Measures of driving performance and neuropsychiatric symptoms were assessed. Results: The FTD patients received more speeding tickets, ran more stop signs and were involved in more off-road crashes and collisions than the controls. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 105 publications
1
39
1
Order By: Relevance
“…The increased recognition of FTD in the elderly has important consequences for dementia care. Compared to AD, patients with FTD often require other strategies for psychosocial support and nursing [2], have no effect of treatments with choline esterase inhibitors or memantin [2], [36], and are unsuitable as drivers at an earlier stage of the disease process compared to AD [37]. As the majority of patients with FTD in SveDem were above 65 years at diagnosis, our findings could also be important in the recruitment of patients for clinical trials.…”
Section: Discussionmentioning
confidence: 82%
“…The increased recognition of FTD in the elderly has important consequences for dementia care. Compared to AD, patients with FTD often require other strategies for psychosocial support and nursing [2], have no effect of treatments with choline esterase inhibitors or memantin [2], [36], and are unsuitable as drivers at an earlier stage of the disease process compared to AD [37]. As the majority of patients with FTD in SveDem were above 65 years at diagnosis, our findings could also be important in the recruitment of patients for clinical trials.…”
Section: Discussionmentioning
confidence: 82%
“…Limited evidence comes from the focal syndromes of the frontotemporal lobe degeneration,12 which, although less frequent than AD, are the second most common cause of early onset dementias 13. A single study on case-series was found in the behavioural variant of frontotemporal dementia (FTD) 14. Fifteen patients with a diagnosis of FTD were administered a driving simulation task, and it was found that, compared to controls, patients with FTD received more speeding tickets, ran more stop signs and were involved in more off-road crashes and collisions than controls.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to ascertain the extent to which drivers are engaging in self-regulation as self-report depends upon the driver's memory of the event, which may be diminished due to cognitive decline, and can change over time. It has been estimated that older drivers with cognitive impairment often overestimate both their driving and functional abilities [42,43] and recent evidence suggests that this lack of accuracy may be correlated with degree of cognitive impairment [43].…”
Section: Discussionmentioning
confidence: 99%